2017
DOI: 10.1007/s00277-017-3084-9
|View full text |Cite
|
Sign up to set email alerts
|

Similar survival outcomes in patients with biclonal versus monoclonal myeloma: a multi-institutional matched case-control study

Abstract: Multiple myeloma is a plasma cell malignancy characterized by clonal proliferation of plasma cells in the bone marrow and associated organ damage. Usually, patients with myeloma present with a single monoclonal protein in serum and/or urine constituted by one heavy chain and one light chain. In less than 5% of the patients, more than one monoclonal protein can be identified. The aim of our retrospective multicenter matched case-control study was to describe the characteristics of cases with biclonal myeloma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Biclonal myeloma and biclonal gammopathy of unknown significance (BGUS) represent rare clinical entities. Their clinical course, therapeutic response, and survival rates do not differ from that of monoclonal gammopathies [7][8][9][10]. The disease is usually diagnosed during diagnostic evaluation for renal failure, anemia, hypercalcemia, or pathological fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Biclonal myeloma and biclonal gammopathy of unknown significance (BGUS) represent rare clinical entities. Their clinical course, therapeutic response, and survival rates do not differ from that of monoclonal gammopathies [7][8][9][10]. The disease is usually diagnosed during diagnostic evaluation for renal failure, anemia, hypercalcemia, or pathological fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Niedokrwistość (52% vs 59%; p = 0,52), uszkodzenie nerek (36% vs 34%; p = 0,83), hiperkalcemia (9% vs 16%; p = 0,28) i zmiany osteolityczne (23% vs 16%; p = 0,38) występowały w obu grupach z podobną częstością. Zarówno biklonalne jak monoklonalne postacie szpiczaka podobnie odpowiadały na leczenie (ORR: 85% vs 90%; p = 0,88), co przekładało się na zbliżone przeżycie w 4-letniej obserwacji (4-letnie OS 72% vs 76%;p = 0,23) [12] (Ryc. 4).…”
Section: Szpiczak Plazmocytowy Z Więcej Niż Jednym Rodzajem Białka Monoklonalnegounclassified
“…However, studies have demonstrated no clinical difference between monoclonal and biclonal gammopathy in terms of patient survival, response to therapy and rate of myeloma-associated anaemia, renal dysfunction or lytic bone lesions. 3,8 The International Myeloma Working Group 2015 criteria for the diagnosis of multiple myeloma suggest the use of serum monoclonal protein concentration in the classification of monoclonal gammopathies but do not address the effect of biclonal isotype-matched (BIM) gammopathy. 9 This study aims to improve understanding of potential biclonal gammopathies of the same heavy and light chain (HLC) combination and to help with consistency of paraprotein reporting in patients being monitored.…”
Section: Introductionmentioning
confidence: 99%